Optimal approach for complete liver tumor ablation using radiofrequency ablation: a simulation study. Issue 2 (4th March 2018) - Givehchi, Sogol; Wong, Yin How; Yeong, Chai Hong; Abdullah, Basri Johan Jeet
Abstract: Purpose: To investigate the effect of radiofrequency ablation (RFA) electrode trajectory on complete tumor ablation using computational simulation. Material and methods: The RFA of a spherical tumor of 2.0 cm diameter along with 0.5 cm clinical safety margin was simulated using Finite Element Analysis software. A total of 86 points inside one-eighth of the tumor volume along the axial, sagittal and coronal planes were selected as the target sites for electrode-tip placement. The angle of the electrode insertion in both craniocaudal and orbital planes ranged from −90° to +90° with 30° increment. The RFA electrode was simulated to pass through the target site at different angles in combination of both craniocaudal and orbital planes before being advanced to the edge of the tumor. Results: Complete tumor ablation was observed whenever the electrode-tip penetrated through the epicenter of the tumor regardless of the angles of electrode insertion in both craniocaudal and orbital planes. Complete tumor ablation can also be achieved by placing the electrode-tip at several optimal sites and angles. Conclusions: Identification of the tumor epicenter on the central slice of the axial images is essential to enhance the success rate of complete tumor ablation during RFA procedures.